Carbapenem-Resistant Klebsiella pneumoniae: Virulence Factors, Molecular Epidemiology and Latest Updates in Treatment Options - Theodoros Karampatakis; Katerina Tsergouli; Payam Behzadi (MDPI AG, 2023)
Klebsiella pneumoniae is a Gram-negative opportunistic pathogen responsible for a variety of community and hospital infections. Infections caused by carbapenem-resistant K. pneumoniae (CRKP) constitute a major threat for public health and are strongly associated with high rates of mortality, especially in immunocompromised and critically ill patients. Adhesive fimbriae, capsule, lipopolysaccharide (LPS), and siderophores or iron carriers constitute the main virulence factors which contribute to the pathogenicity of K. pneumoniae. Colistin and tigecycline constitute some of the last resorts for the treatment of CRKP infections. Carbapenemase production, especially K. pneumoniae carbapenemase (KPC) and metallo-β-lactamase (MBL), constitutes the basic molecular mechanism of CRKP emergence. Knowledge of the mechanism of CRKP appearance is crucial, as it can determine the selection of the most suitable antimicrobial agent among those most recently launched. Plazomicin, eravacycline, cefiderocol, temocillin, ceftolozane-tazobactam, imipenem-cilastatin/relebactam, meropenem-vaborbactam, ceftazidime-avibactam and aztreonam-avibactam constitute potent alternatives for treating CRKP infections. The aim of the current review is to highlight the virulence factors and molecular pathogenesis of CRKP and provide recent updates on the molecular epidemiology and antimicrobial treatment options.